Role Of Announcers In Action Of Criminal Actions For Circular Fake Money - Ahmad Fatah; Gunarto Gunarto (Jurnal Daulat Hukum, 2019)
How investigators determine suspects in criminal cases circulating counterfeit money in the area of Holy Police The way investigators determine suspects in criminal cases circulating counterfeit money in the jurisdiction of the Holy Police is based on fulfilling elements of criminal acts Article 245 of the Criminal Code supported by witnesses and experts and goods evidence, can be added to the confession of the suspect but not absolute.The mechanism for investigating criminal cases circulating money in the territory of the Gubug Police Station has the same operational basis as the mechanism of criminal investigations referring to the SKEP Chief of Police Number Pol: SKEP / 1205 / IX / 2000 concerning the Implementation Manual for Criminal Investigation Processes which states that investigations include: the investigation phase, the prosecution stage (summons, arrests, detention, searches, and seizures), the examination stage (examination of witnesses, experts, suspects), the stage of completing and submitting case files (making resumes, preparing case files, and submitting case files)Obstacles faced by investigators in investigating criminal cases circulating money in the jurisdiction of the Holy Police are internal barriers (limited operational funds of the police, inadequate police personnel is not balanced with the number of crime cases that must be handled, lack of supporting facilities and infrastructure such as forensic laboratories ), and external barriers (lack of community participation in assisting the police in uncovering criminal acts of circulating counterfeit money).Keywords: Investigator; Crime; Currency